Strategic interests in transboundary river cooperation in Southern Africa – the case of the Okavango - Msukwa, Chimwemwe Kanyamana (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Political Science. International Studies))--University of Stellenbosch, 2010.